Daring pirate women - Sharp, Anne Wallace (Minneapolis, Minn. : Lerner Publications Company, 2002)
Profiles pirates throughout history, especially women pirates of Europe, America, and Asia, such as Princess Alvilda, Ingean Ruadh, Grany Imallye, Elizabeth Killigrew, Anne Bonny, and Lai Cho San.
Includes bibliographical references (p. 102) and index.
Keywords: Women pirates -- Biography -- Juvenile literature; Pirates; Women -- Biography